(3JPcQI aj Ydhe GdMOjKs - (3GdhQOj GdeUQj GdcfOj, CHh MaU, GHf GdhQOj, Rjf GdOjf, YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, (B749 (3g`s ((3LeGd GdOjf CHj GdNTGHs)
(3ChdgG (B:s
(3CMeOg Ydi fYeGFg hCTcQg Ydi BdGFg(B... (3hHYO agPg JPcQI aj Ydhe GdMOjK jJfHg HgG GdeHJOj hjSJZfj YfgG GdefJgj(B... (3CbSGeg KdGKI(B...s
(3BNQgG (B:s
(3heYQaI WHbGJ GdQhGI hGdYdeGA hGdehGdj hGdaHGFd(B... (3hgPG BNQ GdJPcQI hgj YLGdI ddeHJOj ajg (B... (3LGeY dahGFO gPG GdYde hThGQOg (B...s
(3fbdJ ef fSNI bQFJ Ydi eDdagGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B5(3, U(B67s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs